2015
DOI: 10.1177/1077695814563981
|View full text |Cite
|
Sign up to set email alerts
|

Journalism Meets Interaction Design

Abstract: As the media industry moves to a post-industrial model, there is a need for journalists-current and future-to have a deeper understanding of the ways that technology impacts their work and how best to produce journalism for mobile and networked devices. This article examines a teaching initiative designed to introduce journalism students to elements of social and mobile technology theory and design practice. Using feedback gained from peers, students, and industry professionals, the initiative was deemed succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Yet there remain conceptual and practical barriers to implementing a converged curriculum, not the least of which involve lack of money for new equipment, lack of money to hire new faculty, and the lack of trained faculty (Tanner & Duhé, 2005). Moreover, as Angus and Doherty (2015) note, "despite the increasingly networked and mobile media landscape, journalism continues to reflect traditional production processes that fail to exploit the potential of new technology" (p. 44).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet there remain conceptual and practical barriers to implementing a converged curriculum, not the least of which involve lack of money for new equipment, lack of money to hire new faculty, and the lack of trained faculty (Tanner & Duhé, 2005). Moreover, as Angus and Doherty (2015) note, "despite the increasingly networked and mobile media landscape, journalism continues to reflect traditional production processes that fail to exploit the potential of new technology" (p. 44).…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing utilization of convergence in media has prompted changes in academia. Studies have suggested that the overall goal of a curriculum based on convergence should be one in which students are prepared both conceptually and practically (Angus & Doherty, 2015; Blom & Davenport, 2012; Wenger & Owens, 2012, 2013). In such a curriculum, students should be taught how to “create an integrated [news] media product, one which combines elements of both print and broadcast within a digital environment” (Kraeplin & Criado, 2005, p.…”
Section: Introductionmentioning
confidence: 99%
“…As for interdisciplinarity, Rogers, Scaife and Rizzo (2005) defined it as 'the emergence of insight and understanding of a problem domain through the integration or derivation of different concepts, methods, and epistemologies from different disciplines in a novel way' (p. 265). Angus and Doherty (2015) summarized that interdisciplinarity involves both collaboration and a transfer of concepts between disciplines. As the integration of journalism and technology in DJ is deep and novel, 'interdisciplinarity' is considered to be most appropriate to describe DJ in this research.…”
Section: Interdisciplinaritymentioning
confidence: 99%
“…We have begun exploring this at the University of Queensland. The Journalism + Interaction Design (J+IxD) initiative (Angus & Doherty, 2015) aims to introduce journalism students to interaction design and there is scope for further curriculum development in this space. If journalists want to be a part of the ubiquitous, tactile future of computing, they will need to be able to think about, and experiment with, new forms of practice.…”
Section: Current and Future Workmentioning
confidence: 99%